KEMANDIRIAN PETANI DALAM BERUSAHATANI SAGU DI DESA TANJUNG KECAMATAN TEBING TINGGI BARAT KEBUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Rahmat Nursodik; Rosnita Rosnita; Eri Sayamar (Universitas Sebelas Maret, 2016)
in the globalization era, farmers should have strong independence and competitiveness. They have to be able to manage their agribusiness to ensure product quality and sustainable agribusiness. The objectives of the research are: to analyze the independence sago farmers in farming in the village of Tanjung, This research was conducted in the village of Tanjung District of Tebing Tinggi Barat Meranti Islands District. 66 farmers serve as respondents to the capture technique respondents using purposive sampling method. Data collected by observation, interviews, and questionnaires. analysis methods used to answer the objectives in this research is methods Likert Scale's Analysis. The results showed: The Independence of farmers in farming sago in the village of Tanjung is independent.